The Impact of Entrepreneurship Education and Entrepreneurial Social Identity on Entrepreneurial Intention of University Students; The Mediating Role of Entrepreneurial Self-Efficacy - Mahdieh Khalili Khezrabadi; Mohammad Hassani (آموزش و مدیریت کارآفرینی)
Promotion of entrepreneurship fields as one of the most important factors of economic development has received more attention from various elements of society. One of the most important measures to develop entrepreneurship among young people is entrepreneurship education in universities. Therefore, this article is written with the aim of investigating and comparing the impact of entrepreneurship training provided by universities as well as the impact of the entrepreneurial and social identity of the students of the Technical and Vocational University on their entrepreneurial intention with regard to the mediating role of entrepreneurial self-efficacy. The measurement tool in this study was a questionnaire that, after verifying its validity and reliability, was given to all students of the Technical and Vocational University of Urmia who had passed the entrepreneurship course in their set of courses. The results of the statistical analysis of 276 questionnaires using SPSS23 and Smart PLS3 software and the structural equation analysis-partial least squares method indicated that the entrepreneurial self-efficacy of students has a mediating role in the relationship between entrepreneurial identity and entrepreneurial intention. However, entrepreneurial education has not been able to, directly or indirectly, have a meaningful relationship with the development of entrepreneurial intentions of students. To make entrepreneurship education more efficient, it is recommended that the Technical and Vocational University considers the connection between such education and individual characteristics, including the social identity of entrepreneurship in students.